Graphene Aerogel Composites with Self-Organized Nanowires-Packed Honeycomb Structure for Highly Efficient Electromagnetic Wave Absorption - You, Xiao; Ouyang, Huiying; Deng, Ruixiang; Zhang, Qiuqi; Xing, Zhenzhong; Chen, Xiaowu; Shan, Qingliang; Yang, Jinshan; Dong, Shaoming (Nano-Micro Letters, 2024)
With vigorous developments in nanotechnology, the elaborate regulation of microstructure shows attractive potential in the design of electromagnetic wave absorbers. Herein, a hierarchical porous structure and composite heterogeneous interface are constructed successfully to optimize the electromagnetic loss capacity. The macro–micro-synergistic graphene aerogel formed by the ice template‑assisted 3D printing strategy is cut by silicon carbide nanowires (SiCnws) grown in situ, while boron nitride (BN) interfacial structure is introduced on graphene nanoplates. The unique composite structure forces multiple scattering of incident EMWs, ensuring the combined effects of interfacial polarization, conduction networks, and magnetic-dielectric synergy. Therefore, the as-prepared composites present a minimum reflection loss value of − 37.8 dB and a wide effective absorption bandwidth (EAB) of 9.2 GHz (from 8.8 to 18.0 GHz) at 2.5 mm. Besides, relying on the intrinsic high-temperature resistance of SiCnws and BN, the EAB also remains above 5.0 GHz after annealing in air environment at 600 °C for 10 h. Highlights: 1 A new strategy for elaborate regulation of microstructure was successfully introduced by the ice template‑assisted 3D printing and chemical vapor deposition strategy, including graphene nanoplate/silicon carbide nanowires hierarchical porous structure and graphene nanoplate/boron nitride composite heterogeneous interface. 2 The composite exhibits excellent electromagnetic wave absorption performance with an RLmin of -37.8 dB and an EABmax of 9.2 GHz (from 8.8 to 18.0 GHz) at 2.5 mm. And the high-temperature absorption stability makes it a promising absorber candidate under high temperature and oxidizing atmosphere.